Hubungan Dukungan Keluarga Pada Ibu Hamil Trimester III Dalam Persiapan Persalinan Aman di Ponkesdes Sumberpetung Ranuyoso Kabupaten Lumajang - Lestari, Dian; Farianingsih, Farianingsih; Rohmatin, Homsiatur (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Childbirth is one of the most special and important experiences in a woman's life. This involves major challenges during the labor preparation process, including physical changes, psychological stress, role transformation, and changes in family structure. Maternity readiness is a condition in which every pregnant woman and her family make prior decisions about the place of birth, service providers, and health facilities, and have selected the main items before giving birth. This study aims to determine the relationship of family support to third trimester pregnant women in preparation for safe delivery at Ponkesdes Sumberpetung Ranuyoso, Lumajang Regency.This study was a correlational design with a cross-sectional approach. The population in this study were all third trimester pregnant women in preparation for safe delivery at Ponkesdes Sumberpetung Ranuyoso, Lumajang Regency, involving 36 participants. The sampling technique used is total sampling. Data was collected using a data collection sheet. Data were analyzed using Predictive Analytics SoftWare Version 18 with the spearman rho test at a significance level of <0.05. The results showed that the third trimester pregnant women at Ponkesdes Sumberpetung Ranuyoso, Lumajang Regency, mostly had family support at a moderate level (63.9%) and more than half had Childbirth Readiness at a fairly optimal level (55.6%). The results of the analysis show that there is a relationship between family support for third trimester pregnant women in preparation for safe delivery with a positive correlation level (p-value = 0.000; r = 0.838). Family support forms adaptive coping for pregnant women because through support by the family it is able to increase self-motivation among mothers so that they are able to take a stand and be able to prepare for childbirth safely.